PHONOLOGICAL AND LEXICAL DESCRIPTION OF MODEBUR LANGUAGE - Ino, La; Mbete, Aron Meko; Dhanawaty, Ni Made; Fernandez, Inyo (e-Journal of Linguistics; Vol. 7. Juli 2013 No. 2, 2013)
This article, in which the theory structural phonology was used, discusses the phonological and lexical description of Modebur language, one of the local languages in Pantar Island. The result of analysis shows that the Modebur language has five vowels; they are /i/, /e/, /a/, /o/, and /u/. They all can distribute in the initial, medial and final position of words. It has sixteen phonemes and sixteen consonants, many of which can distribute in the beginning of words, some can distribute in the initial and medial position of words only, and one can only distribute in the final position of words. The consonants which can distribute completely are /p/, /b/, /m/, /t/, /n/, /s/, /l/, /k/, /?/, /g/, and the ones which can distribute in the initial and medial position of words are /j/, /h/, /w/, and the one which can distribute in the final position of words is /?/.
Keywords: Phonology, Lexicon, Structural